2015
DOI: 10.1016/j.seizure.2015.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy-related deaths: An Australian survey of the experiences and needs of people bereaved by epilepsy

Abstract: Findings highlight the need to improve community understanding and support for those affected by epilepsy and to promote informed risk assessment and communication amongst patients, families and health professionals. People bereaved by epilepsy require both immediate and long-term epilepsy-specific information and support from professionals, informal communities and peer supporters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…For example, saying “epilepsy can kill” is an important message for PWE who are at risk of Sudden Unexpected Death in Epilepsy (SUDEP). 63 However, portraying epilepsy as a lethal condition is unlikely to reduce stigma. For example, one could imagine that employers might be less likely to hire PWE if they think a person can die while having a seizure at work.…”
Section: Discussionmentioning
confidence: 99%
“…For example, saying “epilepsy can kill” is an important message for PWE who are at risk of Sudden Unexpected Death in Epilepsy (SUDEP). 63 However, portraying epilepsy as a lethal condition is unlikely to reduce stigma. For example, one could imagine that employers might be less likely to hire PWE if they think a person can die while having a seizure at work.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed that the possible fatal outcome of a seizure is not known to a considerable amount of participants [5,10]. Even many people who knew someone with epilepsy were not aware of the deadly hazards [21]. Further education should raise awareness of deadly hazards of epilepsy, but at the same time not overemphasise them.…”
Section: Assessment Of Riskmentioning
confidence: 99%
“…Discussing SUDEP risk is an emotive subject. It has been reported that patients and families want to be told what SUDEP is, and the risk factors and riskreduction measures that can be taken [7][8]. However, there does not appear to be consensus from healthcare professionals on whether all patients, or selected patients (e.g.…”
Section: Introductionmentioning
confidence: 99%